PENGELOLAAN MEDIA PEMBELAJARAN DALAM UPAYA MENINGKATKAN HASIL BELAJAR SISWA DI MAN KRECEK PARE KEDIRI - Mustajib (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2018)
Management of instructional media in an effort to improve student learning outcomes in MAN krecek Pare. The purpose of this study were: (1) to describe how teachers plan the development of instructional media in MAN krecek Pare, (2) to determine the organization of the development of instructional media in MAN krecek Pare, (3) to find out how the implementation of the development of instructional media in MAN krecek Pare, (4) to find out how controlling the development of instructional media in MAN krecek Pare Kediri. This study uses qualitative research field with a descriptive-analytic analysis techniques. Collecting data using observation method, interview method and the method of documentation.Data analysis was performed through three stages which include: data reduction, data presentation and conclusion / verification. RESULTS: (1) Using the learning media there are many benefits, among others: (a) learning with instructional media to facilitate and improve the quality of learning, (b) Improve student learning outcomes, (c) Support individual learning according to the ability of students, (d) can be used as a transmitter of direct feedback, (e) the material can be repeated as needed, without causing boredom. Management of instructional media in MAN krecek Pare able to improve perestasi student learning, and this is because by using instructional media students more interested and more motivated, besides using instructional media students who are slow in the power of acceptance can adjust, with their learning program interactive, students can work on the exercises Saol without depending on the teacher, the learning media.